Edukasi Diet Dietary Approaches To Stop Hypertension (Dash) Terhadap Tingkat Pengetahuan Tentang Diet Pada Penderita Hipertensi Di Desa Deli Tua Barat. - GINTING, DANIEL SURANTA; Arianto, Adi; Ginting, Selamat (INSTITUT KESEHATAN DELI HUSADA, 2025)
Hypertension is one of the most common chronic diseases and can be prevented through lifestyle modifications, including dietary management. Public knowledge about proper dietary practices remains low, especially in rural areas. This study aimed to determine the effect of Dietary Approaches to Stop Hypertension (DASH) education on dietary knowledge among individuals with hypertension in Deli Tua Barat Village. A pre-experimental design with a one group pretest-posttest approach was used. A total of 30 participants were selected using purposive sampling. The education was delivered using leaflets adapted to the DASH guidelines. The results showed a significant increase in knowledge scores from pretest to posttest, with a p-value of 0.000. DASH diet education was proven effective in improving patients’ understanding of the importance of dietary regulation. This educational intervention may serve as a practical preventive approach in the community.